Analisis Faktor-Faktor yang Memengaruhi Volume Penjualan pada Perusahaan Subsektor Rokok yang Terdaftar di Bursa Efek Indonesia - Anju Gracya Pramudita Putri; Emma Lilianti; Panca Satria Putra (Jurnal Akuntansi, 2022)
This study aims to test the hypothesis of the effect of promotion costs and production costs on sales volume. The population are cigarette sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique is purposive sampling with the criteria of cigarette companies that have been listed on the Indonesia Stock Exchange, companies that publish complete financial reports from 2016-2021, and companies that have elements of research variables, the number of samples is 2 cigarette companies. The method in this research is quantitative with research data analysis is SPSS. The results of the hypothesis test conclude that there is a simultaneous effect of promotion costs and production costs on sales volume, and partially there is an influence between promotion costs on sales volume and production costs on sales volume, The value of promotion costs tcount > ttable (9.064 > 2.035) with a significance value of 0.000 <0.05, which means Ho is rejected and H1 is accepted. And the value of production costs tcount > ttable (13,146 > 2,035) which means Ho is rejected and H2 is accepted this is proven by the value Fcount > Ftable (84.355 > 3 .28) with a significance value of 0.00 <0.05, which means Ho is rejected and H3 is accepted.Keywords: Promotional Costs, Production Costs, and Sales Volume.